AMBIGUITAS LEKSIKAL DALAM BAHASA INGGRIS DAN BAHASA TALAUD (SEBUAH ANALISIS KONTRASTIF) - Andini, Putri Ayu; Pakasi, Jenny H.; Pelealu, Hetty (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT Lexical ambiguity can be prevented listeners or readers to understand the true meaning of a word because have more meanings. The relationship between one meaning and another can be influenced by figurative factors or only its literal meanings. Thus, the objectives of this study are 1) to identify and classify the forms and types of lexical ambiguity, 2) to analyze the literal meanings and metaphorical extensions in lexical ambiguity, and 3) to describe similarities and differences in lexical ambiguity in English and Talaud. In obtaining English data, writer uses literature review that carried out in the linguistic books of Kreidler (1998), Cruse (1986), and Wolfgang et.al (2013), also the journal English Teaching forum 2018 volume 56 number 1. Meanwhile the data source of Talaud was obtained from the observation, recording, and interviews. Theory used of this research are Cann's (1993: 8) lexical ambiguity theory, Saeed's (2003) literal meaning theory and metaphorical extension, and Brown's (1980) theory of contrastive analysis. The results out of 100 data was found the differences and similiarities of Lexical Ambiguity in English and Talaud language. The finding appears in Polysemy and Homonymy forms. In Polysemy found several factors viz., the factor of representation, cause-effect, and community’s habit. The significant differences arise in the homograph where the meaning in Talaud language can be distinguished on its syllable stress while in English language often caused by different phonetic transcriptions.Keywords: Ambiguity, Metaphorical extensions, Meaning, Talaud Language